THE 1935 CONCORDAT AS A CONSTITUTIONAL-LEGAL CHALLENGE IN THE RELATIONSHIP BETWEEN THE STATE AND THE SERBIAN ORTHODOX CHURCH - Radovanović, Miroslav; Musić, Ivan (Political Review, 2026)
This paper analyzes the Concordat of 1935 as a constitutional and legal challenge in the relations between the state and the Serbian Orthodox Church in the Kingdom of Yugoslavia. It examines the legal, political, religious, and social circumstances surrounding its adoption, with the aim of clarifying the reasons why the Concordat provoked a profound crisis within the state. Particular attention is given to the reactions of the Serbian Orthodox Church and other religious communities, which perceived the Concordat as an act that could grant a privileged position to the Roman Catholic Church within the existing legal framework. By considering the differing interpretations of contemporary legal scholars and political actors, the paper highlights the complexity of the Concordat issue and the persistence of divided opinions regarding its impact on the religious and political life of the Kingdom. The analysis demonstrates that the roots of the crisis were embedded in the constitutional and legal system of a relatively new, multi-confessional, and multi-ethnic state, which faced significant difficulties in reconciling inherited traditions with modern European legal standards. The paper concludes that the Kingdom of Yugoslavia was unable to overcome this constitutional and legal challenge, not only due to widespread public dissatisfaction, but also because of structural limitations inherent in its state organization and legal system.
Keywords: Concordat; Holy See; Serbian Orthodox Church; Milan Stojadinović; Kingdom of Yugoslavia